Artificial Light at Night Impacts the Litter Layer Invertebrate Community With No Cascading Effects on Litter Breakdown - Hey, Melissa H.; Epstein, Howard E.; Haynes, Kyle J. (Frontiers in Ecology and Evolution, 2021)
Artificial light at night (ALAN) can impact the trophic structure of assemblages of ground-dwelling invertebrates, and changes in such assemblages can affect decomposition in terrestrial systems due to the various functional roles of these invertebrates, including microbial grazing, comminution of litter, and predation of other invertebrates, that can directly or indirectly affect plant-litter breakdown. Despite this, we are unaware of any studies that have evaluated the effects of ALAN on the breakdown of plant litter in a terrestrial ecosystem. We sought to answer whether ALAN affects litter breakdown via its effects on a community of ground-dwelling arthropods using two field experiments. In one experiment, we manipulated the presence of ALAN and the size classes of soil invertebrates that could enter mesh bags containing plant litter (litterbags). We found that the rate of plant-litter breakdown increased with the mesh size of litterbags but was unaffected by presence of ALAN. In a second field experiment carried out to examine the effects of ALAN on the trophic structure of litter-layer invertebrate communities, while controlling for potential effects of ALAN on vegetation, we again found that ALAN did not affect litter breakdown despite the fact that ALAN increased the abundances of secondary and tertiary consumers. Our finding that larger assemblages of ground-dwelling secondary and tertiary consumer invertebrates under ALAN did not slow litter breakdown through increased top-down control of detritivores suggests ALAN may disrupt predator-prey interactions in litter-layer communities.